Needs and supporting tools for primary care physicians to improve care of patients with vertigo and dizziness: a national survey - Mantokoudis, Georgios; Zwergal, Andreas; Heg, Dierik; Kerkeni, Hassen; Diener, Suzie; Kalla, Roger; Korda, Athanasia; Candreia, Claudia; Welge-Lüssen, Antje; Tarnutzer, Alexander Andrea (Frontiers in Neurology, 2023)
Background The diagnostic workup and treatment decisions for vertigo or dizziness in primary care can be challenging due to the broad range of possible causes and limited time and expertise of physicians. This can lead to delays in treatment and unnecessary tests. We aimed to identify the unmet needs of primary care physicians (PCPs) and strategies to improve care for dizzy patients. Materials and methods An online survey was conducted among board-certified PCPs in Switzerland to explore needs in caring for dizzy patients and potential educational approaches. Results Based on responses from 152 participating PCPs, satisfaction and confidence were higher in diagnosing (82%) and treating (76%) acute dizziness compared to episodic/chronic cases (63 and 59%, respectively). Younger PCPs had lower diagnostic yield and confidence. Areas for improvement in specialist interactions included communication between physicians (23%/36%; always/often true), shorter waiting times for consultations (19%/40%), more detailed feedback (36%/35%), and consistent patient back referrals (31%/30%). PCPs expressed interest in hands-on courses, workshops, practical guidelines, web-based algorithms, and digital tools such as printed dizzy diaries and apps for follow-up. Conclusion Enhanced dialog between PCPs and specialists is crucial to address the most common unmet needs. Reducing waiting times for referrals and providing clear instructions to specialists for triage are essential. The findings from this survey will guide the development of tools to improve the diagnosis and treatment of dizzy patients. Younger PCPs, who face higher diagnostic uncertainty, should be prioritized for educational approaches such as hands-on courses, workshops, and practical recommendations.